The PARENTS’ ATTITUDES REGARDING CHILDHOOD VACCINATION WITH FOCUS ON ROTAVIRUS VACCINATION IN BISHKEK, KYRGYZSTAN - Kirillova, Iana; Orhun, Nimetcan Mehmet; Ali A. Alabed, Alabed; Salih Mollahaliloğlu, Salih (Malaysian Journal of Public Health Medicine, 2023)
The aim of this study is to determine the parental attitudes regarding childhood vaccinations with focus on rotavirus vaccination. It is a cross-sectional study using the Parent Attitudes about Childhood Vaccines (PACV) questionnaire. This study was conducted among parents, who have at least one child in Bishkek city, Kyrgyzstan, that began on April 4th 2023 - 4th May 2023. At enrollment, parents completed the PACV questionnaire, to screen for vaccine hesitancy. PACV is a questionnaire that includes 15 questions with three factor domains: “General attitudes”, “Behavior” and “Safety and efficacy”. The prevalence of vaccine hesitancy was 21,3% among the participants in this study. Parents had concerns about safety of vaccine shots 19,9%, side effects of rotavirus vaccine 24,8%, efficacy of rotavirus vaccine 13,6% and the number of administered vaccines (18,1% to get fewer vaccines and 29,8% for more shot). This study investigates the differences in childhood and rotavirus vaccine hesitancy by ethnicity (p=0.01) and educational background (p=0.04). The study findings show that there is a vaccine hesitancy among the parents (21,3%) in Bishkek city regarding childhood vaccination and rotavirus vaccine. Concerns of the parents were mostly associated with vaccine shots safety in general, as well as about the side effects and efficacy of rotavirus vaccine.